Phytoplankton community structure in contrasting ecosystems of the Southern Ocean: South Georgia, South Orkneys and western Antarctic Peninsula. (September 2019) - Nunes, Sdena; Latasa, Mikel; Delgado, Maximino; Emelianov, Mikhail; Simó, Rafel; Estrada, Marta
Abstract: The relationships between taxonomy and distribution of the phytoplankton and environmental parameters were studied in four contrasting zones (North of the South Orkney Islands= NSO, Southeast of the South Orkney Islands = SSO, Northwest of South Georgia = NSG and West of Anvers = WA) of the Atlantic sector of the Southern Ocean, during the PEGASO cruise of the BIO Hespérides (January–February 2015). The structure of the phytoplankton community was determined by microscopic examination and by pigment analyses using high-performance liquid chromatography (HPLC) followed by application of the CHEMTAX algorithm. Overall, a statistically significant association was found between fluorometric and HPLC determinations of chlorophyll a, and between chemotaxonomic and microscopy-derived estimates of the contribution of diatoms, dinoflagellates and cryptophytes, although cryptophytes appeared to be underestimated by the microscopic observations. The highest average levels of fluorometric chlorophyll a (517 mg m −2 ) were found at NSG, followed by WA (132 mg m −2 ), NSO (120 mg m −2 ) and SSO (34 mg m −2 ). The phytoplankton community at NSG was dominated by diatoms like Eucampia antarctica and Thalassiosira spp. Cryptophytes and diatoms (mainly Corethron pennatum, small Thalassiosira spp. and Fragilariopsis spp.) were the most abundant chemotaxonomic groups at NSO, followed by haptophytes types 6 + 7, Phaeocystis -like (haptophytes type 8) and, especially in the deeper levels of the euphotic zone, pelagophytes. At SSO, the most important groups were haptophytes types 6 + 7, followed by diatoms (with a combination of taxa similar to that of NSO), Phaeocystis- like and pelagophytes. The main CHEMTAX groups at WA were cryptophytes (between surface and about 40 m depth), haptophytes types 6 + 7 and diatoms. The ratio between the photoprotective pigment diadinoxanthin and the sum of the light harvesting pigments of diadinoxanthin-containing phytoplankton (sum of 19′-butanoyloxyfucoxanthin, 19′-hexanoyloxyfucoxanthin, fucoxanthin and peridinin) was highest at SSO, indicating exposure to a high irradiance environment, and presented a significant positive correlation with the euphotic zone depth. The ratios of the algal osmolyte dimethylsulfoniopropionate and the trace gas dimethylsulfide to chlorophyll a showed the same pattern across zones, highlighting the role of light-related ecophysiology in combination with taxonomy in regulating the production of dimethylated sulfur by plankton communities. Highlights: We used HPLC and microscopy to study phytoplankton communities in the Southern Ocean. Diatoms, cryptophytes and haptophytes were the most important chemotaxonomic groups. Pelagophytes occurred in all study zones and were more abundant in subsurface waters. Photoprotective pigment proportion was positively correlated with euphotic zone depth. High DMSP/Chl a was associated with high irradiance and haptophyte relative abundance.